2021
DOI: 10.17267/2238-2704rpf.v11i1.3412
|View full text |Cite
|
Sign up to set email alerts
|

Interação entre SARS-COV-2 e o sistema Renina Angiotensina

Abstract: A mortalidade ocasionada pela SARS-CoV-2 está associada aos seguintes fatores: Diabetes Mellitus, Hipertensão Arterial Sistêmica (HAS), Doença Arterial Coronariana e idade acima de 70 anos (único fator não modificável) 5 . O processo inflamatório apresenta também associação com a mortalidade após infecção pela SARS-CoV-2. Marcadores inflamatórios elevados, como Proteína C Reativa e Interleucina-6, foram preditores de pior prognóstico 1 .De acordo com a fisiopatologia descrita até então, a SARS-CoV-2 penetra na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…The decrease in renin concentration is justified by an increase in the levels of angiotensin II that decreases the production of renin through negative feedback, determining the balance of this system. 23 Despite this, the study developed by our research group found a median 2-fold higher renin concentration in women who use COC compared with women who do not. 7 The reasons that justify this opposition between the aforementioned studies are unknown.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The decrease in renin concentration is justified by an increase in the levels of angiotensin II that decreases the production of renin through negative feedback, determining the balance of this system. 23 Despite this, the study developed by our research group found a median 2-fold higher renin concentration in women who use COC compared with women who do not. 7 The reasons that justify this opposition between the aforementioned studies are unknown.…”
Section: Discussionmentioning
confidence: 72%
“…23 Aldosterone is a mineralocorticoid, which by binding to the mineralocorticoid receptor on the epithelial cells, recruits sodium channels to the surface of renal epithelial cells, increasing sodium reabsorption, potassium excretion, and plasma volume expansion, culminating in BP elevation. 23 In a literature review carried out in 1996, COCs with high doses of EE (>30mcg) were identified as precursors of SAH, noting a high sodium retention effect in this population. 5 In this regard, so-called low-dose COCs ( 30 mcg of EE) have been formulated in an attempt to decrease the effects of EE on sodium retention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As also Petto [19] et al (2021) speculate that by inactivating ACE2, the virus provides greater activity of ACE1, of the Ang II receptors of the Renin Angiotensin System (RAS) that favors the evolution of diseases and consequently worsen the prognosis of infected patients, since hypertensive and diabetic patients show an increase in inflammatory markers and stimulate the disease cycle with the RAS resulting from the inflammatory process [20,21], responsible for reducing the immune reserve, thus the virus installs easily and aggressively [19,22].…”
Section: Discussionmentioning
confidence: 75%